A history of Chinese political thought - Kim, Youngmin (Polity, 2018)
"China's rapid rise as a regional and global power is one of the most important political developments of the twenty-first century. Yet the West still largely overlooks or oversimplifies the complex ideas and ideals that have shaped China's national and international development from antiquity to the present day. In this beautifully written introductory text, Youngmin Kim offers a uniquely incisive survey of the major themes in Chinese political thought from customary community to empire, exploring their theoretical importance and the different historical contexts in which they arose. Challenging traditional assumptions about Chinese nationalism and Marxist history, Kim shows that 'China' is not a fixed, single identity, but rather a constantly moving target. His probing, interdisciplinary approach traces the long and nuanced history of Chinese thought as a true tradition anchored around certain key themes; many of which began in the early dynasties and still resonate in China today. Only by appreciating the rich history of political thought in China, he argues, can we begin to understand the intricacies and contradictions of Chinese politics, economy and society today"--Provided by publisher.